1998
DOI: 10.1542/peds.102.5.e54
|View full text |Cite
|
Sign up to set email alerts
|

Television and Music Video Exposure and Risk of Adolescent Alcohol Use

Abstract: ABSTRACT. Objective. Alcohol use is frequently portrayed in television programming and advertising. Exposure to media portrayals of alcohol use may lead to increased drinking. To address this issue, we examined prospectively the associations between media exposure and alcohol use in adolescents.Design. Prospective cohort study. Setting. Six public high schools in San Jose, California.Participants. Ninth-grade students (N ‫؍‬ 1533; mean age ‫؍‬ 14.6 years).Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(140 citation statements)
references
References 27 publications
5
132
1
2
Order By: Relevance
“…Further, social media have provided tobacco companies with new opportunities to promote their products 32 and generate favourable attitudes towards tobacco, including intention to smoke, in young non‐smokers 33. In the 1990s and early 2000s televised music videos included significant alcohol and tobacco content 34, 35, 36. However, music videos are now viewed predominantly via on‐line channels such as YouTube, and are another potentially important source of exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Further, social media have provided tobacco companies with new opportunities to promote their products 32 and generate favourable attitudes towards tobacco, including intention to smoke, in young non‐smokers 33. In the 1990s and early 2000s televised music videos included significant alcohol and tobacco content 34, 35, 36. However, music videos are now viewed predominantly via on‐line channels such as YouTube, and are another potentially important source of exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Since the late 1970s much research has thus focused on studying the portrayal of alcohol in popular television entertainment programming, notably television drama serials (soaps) and series, while a significant but less prolific body of research has also emerged into the portrayal of alcohol and drinking in other genres and media, such as film (Cook & Lewington, 1979;Denzin, 1991;Roberts, Henriksen, & Christenson, 1999;Stern, 2005), radio (Pitt, Forrest, Hughes, & Bellis, 2003;Daykin, Irwin, Kimberlee, Orme, Plant, McCarron, et al, 2009), popular music lyrics (Cruz, 1988;Herd, 2005), popular fiction (Cellucci & Larsen, 1995;Greenman, 2000) and music videos (DuRant, Rome, Rich, Allred, Emans, & Woods, 1997;Robinson, Chen, & Killen, 1998;Van den Bulck & Beullens, 2005;Beullens & Van den Bulck, 2008). Given the rapid growth and popularity of the internet, mobile phones and related new media technologies in the last 10-15 years, it is perhaps surprising that only a small number of studies (e.g.…”
Section: Alcohol In Entertainmentmentioning
confidence: 99%
“…Both types of surveys have yielded evidence of significant statistical relationships between selfreported exposure to alcohol advertising and intended future or reported current alcohol consumption (Atkin & Block, 1984a;Atkin, Neuendorf & McDermott, 1983;Robinson, Chen, & Killen, 1998;Connolly, Casswell, Zhang, & Silva, 1994;. Survey studies can be differentiated by the age group studied, with different investigations focusing variously on pre-teenage, teenage or early adulthood samples.…”
Section: Survey Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study of more than 1500 California 9th-graders revealed that increased television and music video viewing was a risk factor for the onset of alcohol use among adolescents. 92 Results of a Columbia University study showed that teenagers who watch more than 3 R-rated films per month are 5 times more likely to drink alcohol compared with teenagers who watch none. 93 Also, in an intriguing study of 2-to 6-yearolds (n ϭ 120) who were asked to roleplay in a make-believe store, children were 5 times more likely to "buy" beer or wine if they had been allowed to see PG-13 or R-rated movies.…”
Section: Drugs In Entertainment Media Cigarettesmentioning
confidence: 99%